2014
DOI: 10.1007/s10585-014-9639-4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the chemokines I-TAC (CXCL11) and SDF-1 (CXCL12) in the regulation of tumor angiogenesis of colorectal cancer

Abstract: The chemokine CXCL12 has a decisive role in tumor progression by mediating pro-angiogenic and pro-metastatic effects through its receptor CXCR4. The CXCL12 pathway is connected with another chemokine, CXCL11, through its second receptor CXCR7. CXCL11 also binds to the CXCR3 receptor. CXCL11 function in tumor angiogenesis is likely receptor dependent because CXCR3 predominantly mediates angiostatic signals whereas CXCR7 mediated signaling is rather angiogenic. We therefore studied the interaction of CXCL12 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…ITAC levels were highly upregulated in treatments when compared to control. ITAC (CXCL11) is known to significantly simulate tumor growth and impart invasive characteristics to the tumor by increasing angiogenesis [66]. The q-RT-PCR studies also revealed marked upregulation in gene expression of survivin and survivin 2B.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…ITAC levels were highly upregulated in treatments when compared to control. ITAC (CXCL11) is known to significantly simulate tumor growth and impart invasive characteristics to the tumor by increasing angiogenesis [66]. The q-RT-PCR studies also revealed marked upregulation in gene expression of survivin and survivin 2B.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Not only CRC cell lines were demonstrated to release CXC-chemokines in response to cytokine stimulation, but also resected tumor explants were found to produce CXC-chemokines under stimulation, even in cases with initially low CXC-levels (26). Among these CXC-chemokines, CXCL11 is deemed to be an important factor during colonic tumorigenesis (5,28). Similar to the results of microarray data analysis, we found that the expression levels of CXCL11 were significantly upregulated in excised tumor specimens compared with normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…C-X-C motif chemokine ligand 11 (CXCL11), released by immune cells during inflammation, is a small cytokine that may contribute to progression of colonic tumorigenesis (5). CXCL11 may regulate the chemotaxis of cells through interaction with a subset of 7-transmembrane, G protein-coupled receptors (6).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that CXCR7 is differentially expressed in colorectal cancer at the transcriptional and protein levels, as well as in the cell membrane (38)(39)(40)(41)(42)(43). CXCR7 expression increased following lipopolysaccharide treatment in the SW480 and COLO 205 colorectal carcinoma cell lines, which express Toll-like receptor 4 (TLR4)/myeloid differential protein-2.…”
Section: Colorectal Cancermentioning
confidence: 99%